Historical grounding, political contexts, material hurdles: Towards more in-depth understandings of `finance going farming' - Sarah Ruth Sippel (Journal of Agrarian Change, 2021)
Two recently published books—Fairbairn's Fields of Gold and Ouma's Farming as a Financial Asset—now provide the first extensive investigations into finance's engagement with farmland. Both books set out to understand finance's growing interest in farmland from the perspective of the financial actors involved, and inquire how, why, and with what kind of challenges `finance has been going farming.' This review essay discusses the two books in the context of the `land rush' literature. It outlines how they contribute to an advanced understanding of the financialization of farmland in three ways, by (i) embedding finance-farmland intersections historically; (ii) scrutinizing the role of the state within financial farmland investments; and (iii) exploring the hurdles involved in `marrying' finance with farmland. I then critically reflect on the areas that have not been covered by the authors. Critical agrarian studies need to investigate how financialization intersects with the digitization of agriculture, examine life expectancies and afterlives of financialized farms, further ground financial investment in concrete rural spaces, and explore individual motivations and belief systems of its proponents more seriously.
Keywords: 630; farmland; financial investment; financialization; land rush